Comparative Effectiveness and Safety Analysis of Dual Antiplatelet Therapies Within an Integrated Delivery System. (August 2017) - Coons, James C.; Iasella, Carlo J.; Chanas, Tyler; Wang, Nan; Williams, Kiersten; Boyd, Anthony; Lyons, John; Eckardt, Jamie; Rihtarchik, Lindsey; Merkel, Alison; Chambers, Alexandra; Lemon, Lara S.; et al.
Background: Dual antiplatelet therapy is a mainstay of care for percutaneous coronary intervention (PCI) patients; however, uncertainty exists in real-world practice about comparative effectiveness and safety outcomes.Objective: To evaluate outcomes of different oral P2Y12 inhibitors in PCI patients.Methods: We retrospectively studied patients treated between July 1, 2010, and December 31, 2013. Patients received clopidogrel, prasugrel, ticagrelor, or more than 1 antiplatelet (switch) during PCI. Outcomes were evaluated for major adverse cardiovascular events (MACE) and bleeding at 1 year. Propensity score matching with Cox proportional hazards analysis was used to determine predictors of MACE and bleeding.Results: A total of 8127 patients were included: clopidogrel (n = 6872), prasugrel (n = 605), ticagrelor (n = 181), and switch (n = 469). Treatment with prasugrel was associated with the lowest risk of MACE using multivariate regression (odds ratio [OR] = 0.57; 95% CI = 0.36-0.92; P = 0.02). In the propensity score–matched analysis, only the prasugrel group was associated with a lower risk of MACE compared with the clopidogrel group. Clopidogrel was associated with the lowest risk of major bleeding using multivariate regression (OR = 0.64; 95% CI = 0.42-0.98; P = 0.042). Both ticagrelor (hazard ratio [HR] = 2.00; 95% CI = 1.11-3.59) and the switch groups (HR = 1.65; 95% CI = 1.09-2.50) were associated with a greater risk of major bleeding compared with clopidogrel. However, no differences were found in the propensity score–matched analysis.Conclusions: Dual antiplatelet therapies differed in both MACE and bleeds in a real-world setting of PCI. Prasugrel was associated with fewer MACE, whereas clopidogrel had fewer major bleeding events.